HOXA9 inhibits migration of lung cancer cells and its hypermethylation is associated with recurrence in non‐small cell lung cancer. Issue 1 (9th May 2014) - Hwang, Jung‐Ah; Lee, Bo Bin; Kim, Yujin; Hong, Seung‐Hyun; Kim, Young‐Ho; Han, Joungho; Shim, Young Mog; Yoon, Chae‐Yeong; Lee, Yeon‐Su; Kim, Duk‐Hwan; Schabath, Matthew B.; DiGiovanni, John
<x xml:space="preserve">Abstract</x> This study was aimed at understanding the clinicopathological significance of HOXA9 hypermethylation in non‐small cell lung cancer (NSCLC). HOXA9 hypermethylation was characterized in six lung cancer cell lines, and its clinicopathological significance was analyzed using methylation‐specific PCR in 271 formalin‐fixed paraffin‐embedded tissues and 27 fresh‐frozen tumor and matched normal tissues from 298 NSCLC patients, and Ki‐67 expression was analyzed using immunohistochemistry. The promoter region of HOXA9 was highly methylated in six lung cancer cell lines, but not in normal bronchial epithelial cells. The loss of expression was restored by treatment of the cells with a demethylating agent, 5‐aza‐2′‐deoxycytidine (5‐Aza‐dC). Transient transfection of HOXA9 into H23 lung cancer cells resulted in the inhibition of cell migration but not proliferation. Conversely, sequence‐specific siRNA‐mediated knockdown of HOXA9 enhanced cell migration. The mRNA levels of HOXA9 in 27 fresh‐frozen tumor tissues were significantly lower than in matched normal tissues (P < 0.0001; Wilcoxon signed‐rank test). HOXA9 hypermethylation was found in 191 (70%) of 271 primary NSCLCs. HOXA9 hypermethylation was not associated with tumor size (P = 0.12) and Ki‐67 proliferation index (P = 0.15). However, patients with HOXA9 hypermethylation had poor recurrence‐free survival (hazard ratio = 3.98, 95% confidence interval = 1.07–17.09, P = 0.01) in never‐smokers, after adjusting for age, sex, tumor size, adjuvant therapy, pathologic stage, and histology. In conclusion, the present study suggests that HOXA9 inhibits migration of lung cancer cells and its hypermethylation is an independent prognostic factor for recurrence‐free survival in never‐smokers with NSCLC. © 2014 Wiley Periodicals, Inc.